Analisis Faktor-Faktor yang Mempengaruhi Minat Pengguna Mobile Banking pada Generasi Z: Pendekatan PLS-SEM - Irgi Arya Sena; Julieta Putri; Nadila Septiliana Putri (CV. Shofanah Media Berkah, 2025)
Ongoing developments in digital technology have driven banks to implement application-based services, positioning mobile banking as a central channel for financial transactions. Nevertheless, Generation Z’s intention to adopt mobile banking differs considerably and is shaped by multiple influencing factors. Using a quantitative approach, this research explores the factors that shape Generation Z’s intention toward mobile banking usage. This study utilized primary data obtained from questionnaires completed by Generation Z participants, which were then examined using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings indicate that some variables significantly affect mobile banking usage intention, while others show no significant impact. These results are expected to provide practical insights for banking institutions in formulating and enhancing digital service strategies that align more closely with the preferences and characteristics of Generation Z.